Structure of the miniature type V-F CRISPR-Cas effector enzyme - Takeda, Satoru N; Nakagawa, Ryoya; Okazaki, Sae; Hirano, Hisato; Kobayashi, Kan; Kusakizako, Tsukasa; Nishizawa, Tomohiro; Yamashita, Keitaro; Nishimasu, Hiroshi; Nureki, Osamu (Molecular cell, 2021)
RNA-guided DNA endonucleases derived from CRISPR-Cas adaptive immune systems are widely used as powerful genome-engineering tools. Among the diverse CRISPR-Cas nucleases, the type V-F Cas12f (also known as Cas14) proteins are exceptionally compact and associate with a guide RNA to cleave single- and double-stranded DNA targets. Here, we report the cryo-electron microscopy structure of Cas12f1 (also known as Cas14a) in complex with a guide RNA and its target DNA. Unexpectedly, the structure revealed that two Cas12f1 molecules assemble with the single guide RNA to recognize the double-stranded DNA target. Each Cas12f1 protomer adopts a different conformation and plays distinct roles in nucleic acid recognition and DNA cleavage, thereby explaining how the miniature Cas12f1 enzyme achieves RNA-guided DNA cleavage as an "asymmetric homodimer." Our findings augment the mechanistic understanding of diverse CRISPR-Cas nucleases and provide a framework for the development of compact genome-engineering tools critical for therapeutic genome editing.